A Stable, Low Permeable TEMPO Catholyte for Aqueous Total Organic Redox Flow Batteries. Issue 8 (18th December 2021) - Hu, Bo; Hu, Maowei; Luo, Jian; Liu, T. Leo
Abstract: Aqueous organic redox flow batteries (AORFBs) are highly attractive for large‐scale energy storage because of their nonflammability, low cost, and sustainability. (2, 2, 6, 6‐Tetramethylpiperidin‐1‐yl)oxyl (TEMPO) derivatives, a class of redox active molecules bearing air‐stable free nitroxyl radicals and high redox potential (>0.8 V vs NHE), has been identified as promising catholytes for AORFBs. However, reported TEMPO based molecules are either permeable through ion exchange membranes or not chemically stable enough for long‐term energy storage. Herein, a new TEMPO derivative functionalized with a dual‐ammonium dicationic group, N 1, N 1, N 1, N 3, N 3, 2, 2, 6, 6‐nonamethyl‐ N 3 ‐(piperidinyloxy)propane‐1, 3‐bis(ammonium) dichloride (N2 ‐TEMPO ) as a stable, low permeable catholyte for AORFBs is reported. Ultraviolet–visible (UV–vis) and proton nuclear magnetic resonance ( 1 H‐NMR) spectroscopic studies reveal its exceptional stability and ultra‐low permeability (1.49 × 10 −12  cm 2  s −1 ). Coupled with 1, 1′‐bis[3‐(trimethylammonio)propyl]‐4, 4′‐bipyridinium tetrachloride ((NPr)2 V) as an anolyte, a 1.35 V N2 ‐TEMPO /(NPr)2 V AORFB with 0.5 m electrolytes (9.05 Wh L −1 ) delivers a high power density of 114 mW cm −2 and 100% capacity retention for 400 cycles at 60 mA cm −2 . At 1.0 m electrolyte concentrations, the N2 ‐TEMPO /(NPr)2 V AORFB achieves an energy density of 18.1 Wh L −1 and capacity retention of 90% for 400 cycles at 60 mA cm −2 . Abstract : A new nitroxyl radical molecule functionalized with a dual‐ammonium dicationic group, N 1, N 1, N 1, N 3, N 3, 2, 2, 6, 6‐nonamethyl‐ N 3 ‐(piperidinyloxy)propane‐1, 3‐bis(ammonium) dichloride (N2 ‐TEMPO) displays exceptional stability and ultra‐low permeability. A 1.35 V N2 ‐TEMPO based flow battery achieves an energy density of 18.1 Wh L −1 and delivers a high power density of 114 mW cm −2 .